Exploration of the causes of poor performance in mathematics in secondary schools at Thulamahashe Circuit - Mathebula, Mkateko Victoria. (My University, 2022)
This study investigated the poor performance of learners in mathematics in a rural secondary schools in Bohlabela District in Mpumalanga province. Mathematics is one of the most critical subjects globally and in Mpumalanga Province of South Africa, specifically. The purpose of this study was to explore the possible causes of poor performance of learners in mathematics in schools. In this study, non-probability sampling was used whereby a purposive sampling strategy was adopted. The participants in this study were secondary school teachers and learners. Twenty mathematics (20) learners participated in this research. These learners were sampled from a pool of 54 Grade 12 learners in one school. Learners were then grouped according to their level of understanding to the subject. The focus was on Grade 12 because it is the exit point of FET. In this study, a case study approach was adopted whereby interviews, documents and observation were used to collect data. The choice of the research design was guided by the following research question: What are the causes of poor performance of Grade 12 learners in mathematics in rural secondary schools? The sub–questions were: What strategies do teachers use to address poor performance of learners in mathematics in Grade 12 in rural secondary schools? What is the role of the department of education in addressing poor performance of learners in mathematics in rural secondary schools? The data analysis involved the generating of themes related to the data collected. In this way, different parts of the narratives were grouped under identified categories. The study found that lack of resources, poor teaching methods, anxiety and attitude towards mathematics contribute to learners’ poor performance in mathematics in Grade 12 in rural secondary schools. The research concludes that teachers should engage learners in more writing activities in order for them to learn effectively and to perform better in mathematics. The study also recommends that teachers should use a variety of teaching methods to teach mathematics and the schools should be well-resourced and teachers should address learners’ anxiety in mathematics to develop the love for mathematics and also enhance positive attitude towards mathematics
Thesis (M.Ed. (Curriculum Studies)) -- University of Limpopo, 2022
Keywords: Grade 12 learners; Mpumalanga Province; Mathematics; Poor performance; Rural secondary schools; Mathematics -- Study and teaching -- South Africa -- Mpumalanga; Academic achievement -- South Africa -- Mpumalanga; High school teaching -- South Africa -- Mpumalanga